[Lava Rock Pillars Along Coast of Snæfellsnes Peninsula] - Streng, Evelyn Fiedler (1975)
Photograph of lava rock pillars along the coast of Snæfellsnes Peninsula in Iceland. The brown, L-shaped rock formation along a pointed grassy cliff in the background. Rocks cover the foreground overlooking the blue ocean. Groups of people stand along the bottom of the photograph and along the rocks ahead.